2021
DOI: 10.1016/j.joto.2020.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Speech perception in noise: Masking and unmasking

Abstract: Speech perception is essential for daily communication. Background noise or concurrent talkers, on the other hand, can make it challenging for listeners to track the target speech (i.e., cocktail party problem). The present study reviews and compares existing findings on speech perception and unmasking in cocktail party listening environments in English and Mandarin Chinese. The review starts with an introduction section followed by related concepts of auditory masking. The next two sections review factors tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 116 publications
(123 reference statements)
0
8
0
Order By: Relevance
“…Previous studies on non-musicians have shown that spatially separating the target speech from the masker facilitates SPiN perception, a phenomenon referred to as “spatial release from masking” (SRM) (for a review, see Wang and Xu (2021) ). Spatially separating stimuli improves perception by allowing binaural processes of interaural time and level differences ( Glyde et al, 2011 ; Yost, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on non-musicians have shown that spatially separating the target speech from the masker facilitates SPiN perception, a phenomenon referred to as “spatial release from masking” (SRM) (for a review, see Wang and Xu (2021) ). Spatially separating stimuli improves perception by allowing binaural processes of interaural time and level differences ( Glyde et al, 2011 ; Yost, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was a mix of two conversations from two couples (one French and one English). This signal corresponds to cocktail party noise (Wang & Xu 2021) to imitate the circumstance where a listener needs to selectively pay attention to specific speech among other concurrent speech. The characteristics are as follows: discontinued, assimilated to long-term average speech spectrum, not understandable.…”
Section: Methodsmentioning
confidence: 99%
“…Here, we used the babble noise, which is a non-stationary noise that works well both as an energetic and informational masker, efficiently reducing intelligibility and speech quality (Brungart, 2001; X. Wang & Xu, 2021). The babble noise was a mixture of five different voices (2 females, 3 males, all native Italian speakers).…”
Section: Methodsmentioning
confidence: 99%
“…We combined the target stories with a five-talker babble to construct stimuli in which the target story was embedded in the noise. Here, we used the babble noise, which is a nonstationary noise that works well both as an energetic and informational masker, efficiently reducing intelligibility and speech quality (Brungart, 2001;X. Wang & Xu, 2021).…”
Section: Stimulimentioning
confidence: 99%